Grisel’s Syndrome: A Case Report - Münevver SERDAROĞLU BEYAZAL; Duygu DEMİROK and Erhan ÇAPKIN and Haydar USUL and Mehmet TOSUN and Ahmet SARI4 (Archives of Rheumatology, 2011)
Grisel’s syndrome is a non-traumatic atlantoaxial subluxation associated with inflammatory conditions of head and neck which occurs primarily in children. Increased flexibility of the ligaments during the inflammation is implicated in the pathogenesis of the subluxation between the axis and atlas. The diagnosis is made by clinical and radiological findings. In this article, we present a 19-year-old male patient who was admitted with a complaint of gradually increasing neck pain and stiffness. He had no history of trauma. Cervical spine radiography and computed tomography revealed atlantoaxial subluxation. Magnetic resonance imaging revealed subluxation and retropharyngeal soft tissue infection. Based on the clinical and radiological findings, we diagnosed the patient as having Grisel’s syndrome, and the patient was treated with intravenous antibiotics and internal immobilization. Although the potential sequelae may be severe, early diagnosis and treatment of Grisel’s syndrome can prevent tragic outcomes.